2021
DOI: 10.1016/j.ijcha.2021.100834
|View full text |Cite
|
Sign up to set email alerts
|

Cross-ethnic comparison of the association between central sleep apnea and atrial fibrillation/flutter: The Kuakini Honolulu-Asia Aging Study and the Osteoporotic Fractures in Men (Mr.OS) study

Abstract: Introduction Few studies indicated the impact of ethnicity on an association between central sleep apnea (CSA) and atrial fibrillation/flutter (AF) in older populations. We assessed possible ethnic differences in the association among elderly Japanese-American and White-American men. Methods We performed a cross-sectional analysis using two population studies of Japanese-American and White-American men. The Kuakini Honolulu-Asia Aging Study is a longitudinal cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The association of the degrees of severity of the OSA (mild, moderate, and severe) with AF can be questioned by studies where it is confirmed, such as that of Gemma Cadby et al [26] or no significant association is found [27,28]. Further studies are needed to see the relationship in this topic.…”
Section: Discussionmentioning
confidence: 98%
“…The association of the degrees of severity of the OSA (mild, moderate, and severe) with AF can be questioned by studies where it is confirmed, such as that of Gemma Cadby et al [26] or no significant association is found [27,28]. Further studies are needed to see the relationship in this topic.…”
Section: Discussionmentioning
confidence: 98%
“…This is crucial given that OSA treatment is recommended as an important component of combined risk factor management by current AF practice guidelines [3] . Although Anzai et al show that CSA/CSR is associated with higher odds of AF [6] , current guidelines do not recommend management of CSA/CSR in AF populations at this timepoint [3] . In the case of predominant CSA/CSR in AF patients, the initial work-up should mainly focus on managing heart failure and other clinical or sub-clinical comorbidities.…”
mentioning
confidence: 99%
“…In this issue of the IJC Heart & Vasculature, Anzai et al performed a cross-sectional analysis using two large population studies: [6] The Kuakini Honolulu-Asia Aging Study, a longitudinal cohort study of Japanese-American men living in Hawaii, and the Osteoporotic Fractures in Men (MrOS) Sleep Study, a longitudinal cohort study of White-American men in the U.S. After adjustment for reported concomitant conditions, CSA and CSR were both associated with higher odds of AF in Japanese-Americans and in White-Americans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep disturbances and sleep disordered breathing (SDB) have been associated widely with cardiovascular diseases [1] , [2] , [3] , [4] , [5] . Also misalignment of the internal circadian time with external physical time due to environmental factors or due to genetic variation in circadian clock genes has been associated with increased incidence of cardiovascular risk factors [6] .…”
mentioning
confidence: 99%